EVALUASI TINGKAT PENERIMAAN SISTEM INFORMASI YUDISIUM MENGGUNAKAN METODE TAM - Sri Handayani; Kusrini Kusrini; M. Rudyanto Arief (Universitas Janabadra, 2017)
This study aims to determine the level of acceptance of judicial Information system at the Bureau of Academic Administration and Student Affairs Muhammadiyah University of Bengkulu. Population in this research are employees of BAAK, Staff of Department, Head Of Departement and students who interact directly with the judicial information system Samples taken as many as 68 respondents using slovin techniques with employee details of 28 people and 40 students. This research was conducted by using Technology Acceptance Model method by distributing questionnaire, with the number of samples were 68 respondents. Data analysis technique is done by using SEM technique and Partial Least Square (PLS) approach. The results showed that the variable Perceived Complexity Using the System positively influenced Attitude Toward Using the System and Behavioral Intention to Use the System. This variable can affect the user acceptance rate of 49.9%. Based on the results of the research, the Administrative Bureau of Academic and Student Affairs (BAAK) and Integrated Service Unit of Computer Information Technology (UPT TIK) of Muhammadiyah University of Bengkulu should improve aspects of Perceived Complexity Using the System, to increase the acceptance level of the judicium information system. Keywords: TAM Method, Evaluation of acceptance level of Yudicium Information System, SIAKAD UMB